A composite electrodeposition nanocatalyst and its preparation method and application in the field of new energy power generation
The composite electrodeposition nanocatalyst is prepared by a new electrodeposition method, and the molybdenum disulfide precursor, modified molybdenum disulfide and carbide modified components are used to solve the problem of high cost of precious metal materials and achieve efficient and low-cost electrolytic hydrogen production catalytic effect.
Patent Information
- Application Number
- CN202411479543.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing electrolytic water hydrogen production catalysts mainly use precious metal materials, which leads to high costs and limits the large-scale development of the hydrogen energy industry.
Using a new electrodeposition method, composite electrodeposition nanocatalysts are prepared by using molybdenum disulfide precursor, modified molybdenum disulfide and carbide as modified components, and the use of precious metal materials is avoided.
The good electrochemical performance of the catalyst is achieved, the catalytic efficiency of hydrogen production by electrolyzing water is improved, the production cost is reduced, and the sustainable development of hydrogen energy is promoted.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water and catalysts, and specifically relates to a composite electrodeposition nanocatalyst and a preparation method thereof and application in the field of new energy power generation. Background Art
[0002] With the continuous growth of global energy demand and the increasingly serious environmental problems, the development and utilization of clean energy has become a key research area for governments and scientific research institutions. Among many clean energy sources, hydrogen energy has attracted much attention due to its high energy density and environmental protection characteristics, and has become an important part of the future energy system. As a key production method of hydrogen energy, the efficiency of water electrolysis directly affects the economy and popularity of hydrogen energy. The catalytic reactions of water electrolysis to produce hydrogen mainly include cathode hydrogen evolution reaction (HER) and anode oxygen evolution reaction (OER). Catalysts play a vital role in this process and can greatly improve the reaction rate and energy efficiency. At present, most catalysts for HER and OER are made of precious metal materials. Although these materials have excellent catalytic performance, their high cost and scarcity seriously restrict the large-scale development of the hydrogen energy industry.
[0003] Electrodeposition technology has attracted wide attention due to its high processing precision, high material utilization rate and easy large-scale production. By preparing catalysts through electrodeposition technology, nanomaterials can be combined with metal substrates to form composite coating catalysts with large specific surface area, which can significantly improve the reaction activity of the catalyst. At the same time, nanomaterials provide more active sites in the catalytic reaction, while the metal substrate can give the catalyst better mechanical strength and conductivity, thereby improving its catalytic performance and long-term stability.
[0004] A Chinese patent (publication number CN117966193A) provides a nickel foam-supported Ru-based catalyst and its preparation method. The catalyst uses nickel foam as a carrier, loaded with active components and additives, the active component is metal ruthenium or ruthenium oxide, and the additive is nano-sheet Mo2N, which improves the electronic transmission performance of the catalyst and enhances the electrolytic water ability of the catalyst. However, the ruthenium used in the patent is relatively expensive, and it still needs to use precious metal materials to achieve good electrochemical performance, which cannot meet the needs of the existing market.
[0005] Therefore, there is an urgent need for a composite electrodeposited nanocatalyst that is prepared using a new electrodeposition method and that avoids the use of precious metal materials by optimizing the composition and structure of the catalyst, thereby overcoming the cost limitations of current typical catalysts, improving its catalytic efficiency in hydrogen production by water electrolysis, and achieving good electrochemical properties of the catalyst, thereby promoting the sustainable development of hydrogen energy. Summary of the invention
[0006] The purpose of the present invention is to provide a composite electrodeposited nanocatalyst and a preparation method thereof and application in the field of renewable energy power generation. By using a molybdenum disulfide precursor, modified molybdenum disulfide and carbide as modified components and adopting a novel electrodeposition method for preparation, good electrochemical properties of the catalyst are ensured without using precious metals.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The first aspect of the present invention provides a method for preparing a composite electrodeposition nanocatalyst, comprising the following steps:
[0009] Step S1: by weight, 10-50 parts of ammonium molybdate and 10-50 parts of sodium sulfide are weighed and added to 100-500 parts of deionized water, and ultrasonically stirred for 0.5-1 h, and then 0.1-0.5 parts of sodium dodecyl sulfate are added, and stirred for 2-3 h to obtain a mixed solution;
[0010] Step S2: transferring the mixed solution described in step S1 to a reactor for hydrothermal reaction, centrifuging after the reaction is completed, washing the separated precipitate with deionized water, and drying to obtain a molybdenum disulfide precursor;
[0011] Step S3: In parts by weight, 10 to 50 parts of nickel sulfate hexahydrate, 1 to 5 parts of cobalt chloride hexahydrate, 10 to 50 parts of ammonium chloride, 10 to 50 parts of boric acid, 10 to 50 parts of sodium hypophosphite and 0.1 to 0.5 parts of sodium dodecyl sulfate are weighed and added to 1000 to 2000 parts of deionized water, and after stirring evenly, 1 to 5 parts of molybdenum disulfide precursor, 1 to 3 parts of modified molybdenum disulfide and 1 to 2 parts of carbide are added, and stirred for 1 to 2 hours to obtain an electrolyte;
[0012] Step S4: using a 10×10 mm nickel foam as a cathode, a 20×20 mm nickel plate as an anode, and the electrolyte described in step S3 to form an electrodeposition system, and performing an electrodeposition reaction for 1 to 5 minutes under a 0.1 to 0.5 A constant current DC power supply;
[0013] Step S5: After the electrodeposition reaction in step S4 is completed, the cathode is recovered and washed with anhydrous ethanol and deionized water in sequence, and then the cathode is heat-treated to obtain a composite electrodeposition nanocatalyst.
[0014] As a preferred solution, the reaction temperature of the hydrothermal reaction in step S2 is 120-200° C., and the reaction time is 6-16 hours; the drying temperature is 60-90° C., and the time is 12-24 hours.
[0015] As a preferred solution, the modified molybdenum disulfide in step S3 is carbon-modified molybdenum disulfide and oxygen-modified molybdenum disulfide; the mass ratio of the carbon-modified molybdenum disulfide to the oxygen-modified molybdenum disulfide is (1~2):1.
[0016] As a preferred solution, the preparation method of the carbon-modified molybdenum disulfide is as follows: by weight, 3 to 5 parts of sulfur powder are weighed and added to 12 to 15 parts of octylamine. After stirring for 5 to 10 minutes, 8 to 10 parts of molybdenum trioxide and 15 to 20 parts of anhydrous ethanol are added and stirred for 10 to 20 minutes to obtain a light yellow solution. The light yellow solution is maintained at 150 to 160°C for 24 to 36 hours, cooled to room temperature, washed with deionized water, and then dried at 60 to 70°C under vacuum for 12 to 18 hours to obtain a primary product; 40 to 50 parts of the primary product and 60 to 80 parts of glucose are weighed and added to 100 to 120 parts of anhydrous ethanol, first ultrasonicated for 0.5 to 1 hour, then stirred for 1 to 2 hours, and the precipitate is collected by centrifugation; the precipitate is dried at 60 to 70°C under vacuum for 10 to 12 hours, and then heated to 700 to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, maintained for 2 to 3 hours, and cooled to room temperature to obtain carbon-modified molybdenum disulfide.
[0017] During the preparation process of carbon-modified molybdenum disulfide, octylamine is carbonized, condensed, aggregated and agglomerated to form a carbon layer which is embedded in the molybdenum disulfide layers. At the same time, glucose is evenly dispersed in the molybdenum disulfide during the ultrasonic process and then forms a conductive network on the surface after high-temperature carbonization. The carbon element and molybdenum disulfide have a good synergistic coupling effect, which is beneficial to the stable dispersion of catalytically active nanoparticles and improves the utilization rate of active sites, thereby improving the electrochemical performance of the catalyst.
[0018] As a preferred scheme, the preparation method of the oxygen-modified molybdenum disulfide is as follows: in parts by weight, 10 to 30 parts of ethylene glycol are added to 40 to 60 parts of deionized water, and after stirring evenly, 2 to 4 parts of ammonium molybdate and 6 to 7 parts of thiourea are added, and stirred for 1 to 2 hours to obtain a mixed solution; the mixed solution is reacted at 200 to 220° C. for 16 to 20 hours, and after the reaction is completed, the product is washed with deionized water, and then vacuum dried at 60 to 80° C. for 6 to 8 hours to obtain oxygen-modified molybdenum disulfide.
[0019] Oxygen-modified molybdenum disulfide adjusts the electronic structure of molybdenum disulfide by doping oxygen atoms into it and replacing sulfur atoms with oxygen atoms. On the one hand, it can adjust the active sites of the catalyst to produce more active unsaturated sulfur atoms in a more disordered structure. On the other hand, it can improve the conductivity of the catalyst by doping, thereby improving the electrochemical performance of the catalyst.
[0020] As a preferred solution, the carbides in step S3 are tungsten carbide and molybdenum carbide; the mass ratio of tungsten carbide to molybdenum carbide is (1-2):1.
[0021] The carbides used are tungsten carbide and molybdenum carbide. Since carbon atoms are introduced into tungsten atoms and molybdenum atoms, their electronic structure is very similar to the precious metal platinum, which is an ideal choice for water decomposition to produce hydrogen. At the same time, due to the presence of ultrafine nanocrystals, conductive porous carbon and rich active sites in carbides, the electrochemical properties of nanocatalysts can be effectively enhanced through the compound use of tungsten carbide and molybdenum carbide.
[0022] As a preferred solution, the nickel foam in step S4 is boron-modified nickel foam; the preparation method of the boron-modified nickel foam is: in parts by weight, 35-40 parts of ammonia water, 50-60 parts of ammonium chloride, 10-15 parts of cobalt chloride and 8-10 parts of nickel chloride are added to 150-200 parts of deionized water, and stirred evenly to obtain a mixed solution A; 10-20 parts of sodium borohydride and 8-10 parts of sodium hydroxide are added to 150-200 parts of deionized water, and stirred evenly to obtain a mixed solution B; 10-20 parts of nickel foam are soaked in 150-200 parts of mixed solution A for 5-10 minutes, and then 150-200 parts of mixed solution B are added, and the reaction is carried out for 10-20 minutes. After the reaction is completed, the product is washed with deionized water, and then dried at 30-35° C. under vacuum conditions for 24-30 hours to obtain the boron-modified nickel foam.
[0023] The radius of the boron atom in the boron-modified nickel foam is small, and it is easy to fill the lattice gap of the nickel foam when forming a complex, maintaining the original bonding mode of nickel, and the metallic properties of nickel are not changed; at the same time, the electron transfer between boron and nickel can slow down the oxidation of the metal, and the unique electronic structure can reduce the kinetic energy barrier in the electrochemical process; in addition, the introduction of boron can regulate the surface chemical activity of the nickel foam, enhance the catalytic activity and selectivity; through the comprehensive effect of multiple aspects, the electrochemical properties of the nanocatalyst are improved.
[0024] As a preferred solution, the heat treatment temperature in step S5 is 60-90° C. and the time is 2-6 hours.
[0025] The second aspect of the present invention provides a composite electrodeposition nanocatalyst prepared by the preparation method described in the first aspect.
[0026] The third aspect of the present invention provides an application of a composite electrodeposited nanocatalyst prepared by the preparation method described in the first aspect in the field of new energy power generation.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention adopts a new and improved nanocomposite electrodeposition technology. In the process of co-deposition of nanoparticles and metal ions, nanoparticles are embedded in a metal coating to prepare a catalyst with a composite coating. The catalyst has a multilayer structure, which not only has the unique physical and chemical properties of nanoparticles, but also has the excellent performance of metal coatings. This catalyst with a composite coating not only exhibits high catalytic activity and efficiency, but also has excellent stability, and can effectively maintain its catalytic performance during long-term use, meeting the needs of industrial applications.
[0029] 2. The present invention modifies molybdenum disulfide and uses carbon-modified molybdenum disulfide and oxygen-modified molybdenum disulfide in combination. On the one hand, the carbon element in the carbon-modified molybdenum disulfide and the molybdenum disulfide have a good synergistic coupling effect, which is beneficial to the stable dispersion of catalytically active nanoparticles. On the other hand, the oxygen-modified molybdenum disulfide produces more active unsaturated sulfur atoms in the disordered structure by doping oxygen atoms into molybdenum disulfide. The combined effect improves the electrochemical performance of the catalyst.
[0030] 3. The present invention uses tungsten carbide and molybdenum carbide in combination. Since carbon atoms are introduced into tungsten atoms and molybdenum atoms, their electronic structure is very similar to that of the precious metal platinum, which is an ideal choice for water decomposition to produce hydrogen. At the same time, due to the presence of ultrafine nanocrystals, conductive porous carbon and abundant active sites in carbides, the electrochemical properties of nanocatalysts can be effectively enhanced by using tungsten carbide and molybdenum carbide in combination.
[0031] 4. The boron atomic radius in the boron-modified nickel foam of the present invention is relatively small, and it is easy to fill the lattice gap of the nickel foam when forming a composite, maintaining the original bonding mode of nickel, and the metallic properties of nickel are not changed; at the same time, the electron transfer between boron and nickel can slow down the oxidation of the metal, and the unique electronic structure can reduce the kinetic energy barrier in the electrochemical process; in addition, the introduction of boron can regulate the surface chemical activity of the nickel foam, enhance the catalytic activity and selectivity; through the comprehensive effects of multiple aspects, the electrochemical properties of the nanocatalyst are improved. DETAILED DESCRIPTION
[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The sources of some components in the embodiments and comparative examples are as follows:
[0034] Ammonium molybdate, product number S104871, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0035] Sodium sulfide, product number S823448, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0036] Sodium dodecyl sulfate, CAS No. 151-21-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0037] Sulfur powder, product number S817643, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0038] Octylamine, CAS No. 111-86-4, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0039] Molybdenum trioxide, product number M104354, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0040] Anhydrous ethanol, CAS No. 64-17-5, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0041] Glucose, CAS No. 50-99-7, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0042] Ethylene glycol, CAS No. 107-21-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0043] Ammonium molybdate, product number S104871, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0044] Thiourea, product number T112512, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;
[0045] Tungsten carbide, CAS No. 12070-12-1, purchased from Xiamen Jinlu Special Alloy Co., Ltd.;
[0046] Molybdenum carbide, CAS No. 12069-89-5, was purchased from Suzhou Beike Nano Co., Ltd.;
[0047] Nickel sulfate hexahydrate, product number N4882, was purchased from Sigma-Aldrich (Shanghai) Trading Co., Ltd.;
[0048] Cobalt chloride hexahydrate, CAS No. 7791-13-1, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0049] Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0050] Sodium hypophosphite, CAS No. 7681-53-0, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0051] Ammonia water, CAS No. 1336-21-6, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0052] Ammonium chloride, CAS No. 12125-02-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0053] Cobalt chloride, CAS No. 7646-79-9, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0054] Nickel chloride, CAS No. 7718-54-9, purchased from Hubei Kewode Chemical Co., Ltd.;
[0055] Sodium borohydride, CAS No. 16940-66-2, was purchased from Shanghai Fulian Chemical Reagent Co., Ltd.;
[0056] Sodium hydroxide, CAS No. 1310-73-2, was purchased from Sinopharm Chemical Reagent Co., Ltd.;
[0057] Commercially available nickel foam, item number BEF-NI-008, was purchased from Suzhou Qiandingli Electronic Technology Co., Ltd.
[0058] Example 1
[0059] This embodiment provides a method for preparing a composite electrodeposition nanocatalyst, comprising the following steps:
[0060] Preparation of carbon-modified molybdenum disulfide: 5 parts of sulfur powder were weighed by weight and added to 15 parts of octylamine. After stirring for 10 minutes, 10 parts of molybdenum trioxide and 20 parts of anhydrous ethanol were added and stirred for 20 minutes to obtain a light yellow solution. The light yellow solution was kept at 160°C for 24 hours, cooled to room temperature, washed with deionized water, and then dried at 70°C under vacuum for 12 hours to obtain a primary product; 50 parts of the primary product and 80 parts of glucose were weighed and added to 120 parts of anhydrous ethanol, first ultrasonicated for 1 hour, then stirred for 2 hours, and the precipitate was collected by centrifugation; the precipitate was dried at 70°C under vacuum for 10 hours, and then heated to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept for 2 hours, and cooled to room temperature to obtain carbon-modified molybdenum disulfide.
[0061] Preparation of oxygen-modified molybdenum disulfide: In parts by weight, 30 parts of ethylene glycol are added to 60 parts of deionized water, and after stirring evenly, 4 parts of ammonium molybdate and 7 parts of thiourea are added, and stirred for 2 hours to obtain a mixed solution; the mixed solution is reacted at 220°C for 16 hours. After the reaction is completed, the product is washed with deionized water, and then vacuum dried at 80°C for 6 hours to obtain oxygen-modified molybdenum disulfide.
[0062] Preparation of boron-modified nickel foam: In parts by weight, 40 parts of ammonia water, 60 parts of ammonium chloride, 15 parts of cobalt chloride and 10 parts of nickel chloride are added to 200 parts of deionized water, and stirred to obtain a mixed solution A; 20 parts of sodium borohydride and 10 parts of sodium hydroxide are added to 200 parts of deionized water, and stirred to obtain a mixed solution B; 20 parts of nickel foam are soaked in 200 parts of mixed solution A for 10 minutes, and then 200 parts of mixed solution B are added and reacted for 20 minutes. After the reaction is completed, the product is washed with deionized water and then dried under vacuum conditions at 35°C for 24 hours to obtain boron-modified nickel foam.
[0063] Step S1: by weight, 50 parts of ammonium molybdate and 50 parts of sodium sulfide were weighed and added to 500 parts of deionized water, and ultrasonically stirred for 1 hour, and then 0.5 parts of sodium dodecyl sulfate were added and stirred for 3 hours to obtain a mixed solution;
[0064] Step S2: The mixed solution described in step S1 is transferred to a reactor for hydrothermal reaction (reaction temperature is 200°C, time is 6h), and after the reaction is completed, centrifugation is performed, and the separated precipitate is washed with deionized water and dried (drying temperature is 90°C, time is 12h) to obtain a molybdenum disulfide precursor;
[0065] Step S3: In parts by weight, 50 parts of nickel sulfate hexahydrate, 5 parts of cobalt chloride hexahydrate, 50 parts of ammonium chloride, 50 parts of boric acid, 50 parts of sodium hypophosphite and 0.5 parts of sodium dodecyl sulfate are weighed and added to 2000 parts of deionized water, and after stirring evenly, 5 parts of molybdenum disulfide precursor, 3 parts of modified molybdenum disulfide (the mass ratio of carbon-modified molybdenum disulfide to oxygen-modified molybdenum disulfide is 2:1) and 2 parts of carbide (the mass ratio of tungsten carbide to molybdenum carbide is 1:1) are added, and stirred for 2 hours to obtain an electrolyte;
[0066] Step S4: using a 10×10 mm boron-modified nickel foam as a cathode, a 20×20 mm nickel plate as an anode, and the electrolyte described in step S3 to form an electrodeposition system, and performing an electrodeposition reaction for 5 min under a 0.1 A constant current DC power supply;
[0067] Step S5: After the electrodeposition reaction in step S4 is completed, the cathode is recovered and washed with anhydrous ethanol and deionized water in sequence, and then the cathode is heat-treated (heat treatment temperature is 90° C., time is 2 h) to obtain a composite electrodeposition nanocatalyst.
[0068] Example 2
[0069] This embodiment provides a method for preparing a composite electrodeposition nanocatalyst, comprising the following steps:
[0070] Preparation of carbon-modified molybdenum disulfide: 3 parts of sulfur powder were weighed by weight and added to 12 parts of octylamine. After stirring for 5 minutes, 8 parts of molybdenum trioxide and 15 parts of anhydrous ethanol were added and stirred for 10 minutes to obtain a light yellow solution. The light yellow solution was kept at 150°C for 36 hours, cooled to room temperature, washed with deionized water, and then dried at 60°C under vacuum for 18 hours to obtain a primary product; 40 parts of the primary product and 60 parts of glucose were weighed and added to 100 parts of anhydrous ethanol, first ultrasonicated for 0.5 hours, then stirred for 1 hour, and the precipitate was collected by centrifugation; the precipitate was dried at 60°C under vacuum for 12 hours, and then heated to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept for 3 hours, and cooled to room temperature to obtain carbon-modified molybdenum disulfide.
[0071] Preparation of oxygen-modified molybdenum disulfide: In parts by weight, 10 parts of ethylene glycol are added to 40 parts of deionized water, and after stirring evenly, 2 parts of ammonium molybdate and 6 parts of thiourea are added, and stirred for 1 hour to obtain a mixed solution; the mixed solution is reacted at 200°C for 20 hours. After the reaction is completed, the product is washed with deionized water, and then vacuum dried at 60°C for 6 hours to obtain oxygen-modified molybdenum disulfide.
[0072] Preparation of boron-modified nickel foam: In parts by weight, 35 parts of ammonia water, 50 parts of ammonium chloride, 10 parts of cobalt chloride and 8 parts of nickel chloride are added to 150 parts of deionized water, and stirred evenly to obtain a mixed solution A; 10 parts of sodium borohydride and 8 parts of sodium hydroxide are added to 150 parts of deionized water, and stirred evenly to obtain a mixed solution B; 10 parts of nickel foam are soaked in 150 parts of mixed solution A for 5 minutes, and then 150 parts of mixed solution B are added, and the reaction is carried out for 10 minutes. After the reaction is completed, the product is washed with deionized water, and then dried under vacuum conditions at 30°C for 30 hours to obtain boron-modified nickel foam.
[0073] Step S1: by weight, 10 parts of ammonium molybdate and 10 parts of sodium sulfide were weighed and added to 100 parts of deionized water, and ultrasonically stirred for 0.5 h, and then 0.1 parts of sodium dodecyl sulfate were added and stirred for 2 h to obtain a mixed solution;
[0074] Step S2: The mixed solution described in step S1 is transferred to a reactor for hydrothermal reaction (reaction temperature is 120°C, time is 16 hours), and after the reaction is completed, centrifugation is performed, and the separated precipitate is washed with deionized water and dried (drying temperature is 60°C, time is 24 hours) to obtain a molybdenum disulfide precursor;
[0075] Step S3: In parts by weight, 10 parts of nickel sulfate hexahydrate, 1 part of cobalt chloride hexahydrate, 10 parts of ammonium chloride, 10 parts of boric acid, 10 parts of sodium hypophosphite and 0.1 part of sodium dodecyl sulfate are weighed and added to 1000 parts of deionized water, and after stirring evenly, 1 part of molybdenum disulfide precursor, 1 part of modified molybdenum disulfide (the mass ratio of carbon-modified molybdenum disulfide to oxygen-modified molybdenum disulfide is 1:1) and 1 part of carbide (the mass ratio of tungsten carbide to molybdenum carbide is 1:1) are added, and stirred for 1 hour to obtain an electrolyte;
[0076] Step S4: using a 10×10 mm boron-modified nickel foam as a cathode, a 20×20 mm nickel plate as an anode, and the electrolyte described in step S3 to form an electrodeposition system, and performing an electrodeposition reaction for 5 min under a 0.1 A constant current DC power supply;
[0077] Step S5: After the electrodeposition reaction in step S4 is completed, the cathode is recovered and washed with anhydrous ethanol and deionized water in sequence, and then the cathode is heat-treated (heat treatment temperature is 60° C., time is 6 h) to obtain a composite electrodeposition nanocatalyst.
[0078] Example 3
[0079] This embodiment provides a method for preparing a composite electrodeposition nanocatalyst, comprising the following steps:
[0080] Preparation of carbon-modified molybdenum disulfide: 4 parts of sulfur powder were weighed by weight and added to 13 parts of octylamine. After stirring for 8 minutes, 9 parts of molybdenum trioxide and 18 parts of anhydrous ethanol were added and stirred for 16 minutes to obtain a light yellow solution. The light yellow solution was kept at 155°C for 28 hours, cooled to room temperature, washed with deionized water, and then dried at 68°C under vacuum for 15 hours to obtain a primary product; 48 parts of the primary product and 75 parts of glucose were weighed and added to 110 parts of anhydrous ethanol, first ultrasonicated for 1 hour, then stirred for 1 hour, and the precipitate was collected by centrifugation; the precipitate was dried at 65°C under vacuum for 11 hours, and then heated to 760°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept for 2 hours, and cooled to room temperature to obtain carbon-modified molybdenum disulfide.
[0081] Preparation of oxygen-modified molybdenum disulfide: In parts by weight, 25 parts of ethylene glycol are added to 53 parts of deionized water, and after stirring evenly, 3 parts of ammonium molybdate and 7 parts of thiourea are added, and stirred for 2 hours to obtain a mixed solution; the mixed solution is reacted at 210°C for 18 hours. After the reaction is completed, the product is washed with deionized water and then vacuum dried at 75°C for 7 hours to obtain oxygen-modified molybdenum disulfide.
[0082] Preparation of boron-modified nickel foam: In parts by weight, 38 parts of ammonia water, 56 parts of ammonium chloride, 14 parts of cobalt chloride and 9 parts of nickel chloride are added to 180 parts of deionized water, and stirred evenly to obtain a mixed solution A; 17 parts of sodium borohydride and 9 parts of sodium hydroxide are added to 180 parts of deionized water, and stirred evenly to obtain a mixed solution B; 16 parts of nickel foam are soaked in 180 parts of mixed solution A for 8 minutes, and then 180 parts of mixed solution B are added and reacted for 15 minutes. After the reaction is completed, the product is washed with deionized water and then dried under vacuum conditions at 32°C for 28 hours to obtain boron-modified nickel foam.
[0083] Step S1: by weight, 35 parts of ammonium molybdate and 30 parts of sodium sulfide were weighed and added to 400 parts of deionized water, and ultrasonically stirred for 1 hour, and then 0.3 parts of sodium dodecyl sulfate were added and stirred for 2.5 hours to obtain a mixed solution;
[0084] Step S2: The mixed solution described in step S1 is transferred to a reactor for hydrothermal reaction (reaction temperature is 180°C, reaction time is 10h), centrifuged after the reaction is completed, and the separated precipitate is washed with deionized water and dried (drying temperature is 90°C, time is 18h) to obtain a molybdenum disulfide precursor;
[0085] Step S3: In parts by weight, 40 parts of nickel sulfate hexahydrate, 3 parts of cobalt chloride hexahydrate, 35 parts of ammonium chloride, 38 parts of boric acid, 42 parts of sodium hypophosphite and 0.2 parts of sodium dodecyl sulfate are weighed and added to 1500 parts of deionized water, and after stirring evenly, 4 parts of molybdenum disulfide precursor, 2 parts of modified molybdenum disulfide (the mass ratio of carbon-modified molybdenum disulfide to oxygen-modified molybdenum disulfide is 1:1) and 1.5 parts of carbide (the mass ratio of tungsten carbide to molybdenum carbide is 2:1) are added, and stirred for 2 hours to obtain an electrolyte;
[0086] Step S4: using a 10×10 mm boron-modified nickel foam as a cathode, a 20×20 mm nickel plate as an anode, and the electrolyte described in step S3 to form an electrodeposition system, and performing an electrodeposition reaction for 3 min under a 0.3 A constant current DC power supply;
[0087] Step S5: After the electrodeposition reaction in step S4 is completed, the cathode is recovered and washed with anhydrous ethanol and deionized water in sequence, and then the cathode is heat-treated (heat treatment temperature is 80° C., time is 4 h) to obtain a composite electrodeposition nanocatalyst.
[0088] Comparative Example 1
[0089] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that commercially available nickel foam is used instead of boron-modified nickel foam, and modified molybdenum disulfide and carbide are not used in step S3. The rest is the same as Example 1.
[0090] Comparative Example 2
[0091] This comparative example provides a method for preparing a composite electrodeposited nanocatalyst. The difference between this comparative example and Example 1 is that commercially available nickel foam is used instead of boron-modified nickel foam, and carbide is not used in step S3. The rest is the same as Example 1.
[0092] Comparative Example 3
[0093] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that commercially available nickel foam is used instead of boron-modified nickel foam, and modified molybdenum disulfide is not used in step S3. The rest is the same as Example 1.
[0094] Comparative Example 4
[0095] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that modified molybdenum disulfide and carbide are not used in step S3, and the rest is the same as Example 1.
[0096] Comparative Example 5
[0097] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that commercially available nickel foam is used instead of boron-modified nickel foam, and the rest is the same as Example 1.
[0098] Comparative Example 6
[0099] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that no carbide is used in step S3, and the rest is the same as Example 1.
[0100] Comparative Example 7
[0101] This comparative example provides a method for preparing a composite electrodeposition nanocatalyst. The difference between this comparative example and Example 1 is that modified molybdenum disulfide is not used in step S3, and the rest is the same as Example 1.
[0102] Performance Testing
[0103] The catalysts prepared in the above examples and comparative examples were subjected to the following tests:
[0104] Electrochemical performance test: a KOH solution with a molar concentration of 1 mol / L was prepared, sealed and placed in a dark place. Before conducting the electrochemical test, high-purity nitrogen or argon was introduced into the solution to remove dissolved oxygen in the water. A CHI 660e electrochemical workstation was used, and a three-electrode system was selected to test the catalyst. In the three-electrode system, a platinum sheet was used as a counter electrode, a saturated calomel electrode was used as a reference electrode, and the catalyst of the embodiment and the comparative example was used as a working electrode. Linear sweep voltammetry (LSV) was used at a scanning speed of 1 mV / s in a 1 mol / L KOH aqueous solution to detect its oxygen evolution catalytic performance for water decomposition. All tests were conducted at room temperature.
[0105] Table 1 Performance test results
[0106]
[0107] From the above performance test results, it can be seen that the catalysts of Examples 1-3 have good effects, especially Example 1 has the most outstanding comprehensive performance, 10mA·cm -2 The overpotential is 215mV, 500mA·cm -2 The overpotential is 297 mV, which is mainly because it is prepared by using molybdenum disulfide precursor, modified molybdenum disulfide and carbide as modifying components and a new electrodeposition method to ensure good electrochemical performance of the catalyst.
[0108] The comparative example does not adopt the necessary technical solution, resulting in that the corresponding performance test is significantly worse than that of the embodiment. Compared with Example 1, Comparative Example 1 uses commercially available nickel foam instead of boron-modified nickel foam, and modified molybdenum disulfide and carbide are not used in step S3, so the overpotential increases; Compared with Example 1, Comparative Example 2 uses commercially available nickel foam instead of boron-modified nickel foam, and carbide is not used in step S3, so the overpotential increases; Compared with Example 1, Comparative Example 3 uses commercially available nickel foam instead of boron-modified nickel foam, and carbide is not used in step S3, so the overpotential increases. In the nickel foam, modified molybdenum disulfide is not used in step S3, and the overpotential increases; compared with Example 1, in comparative example 4, modified molybdenum disulfide and carbide are not used in step S3, and the overpotential increases; compared with Example 1, in comparative example 5, commercially available nickel foam is used to replace boron-modified nickel foam, and the overpotential increases; compared with Example 1, in comparative example 6, carbide is not used in step S3, and the overpotential increases; compared with Example 1, in comparative example 7, modified molybdenum disulfide is not used in step S3, and the overpotential increases. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0109] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a composite electrodeposition nanocatalyst, characterized in that: The preparation method comprises the following steps: Step S1: by weight, 10-50 parts of ammonium molybdate and 10-50 parts of sodium sulfide are weighed and added to 100-500 parts of deionized water, and ultrasonically stirred for 0.5-1 h, and then 0.1-0.5 parts of sodium dodecyl sulfate are added, and stirred for 2-3 h to obtain a mixed solution; Step S2: transferring the mixed solution described in step S1 to a reactor for hydrothermal reaction, centrifuging after the reaction is completed, washing the separated precipitate with deionized water, and drying to obtain a molybdenum disulfide precursor; Step S3: In parts by weight, 10 to 50 parts of nickel sulfate hexahydrate, 1 to 5 parts of cobalt chloride hexahydrate, 10 to 50 parts of ammonium chloride, 10 to 50 parts of boric acid, 10 to 50 parts of sodium hypophosphite and 0.1 to 0.5 parts of sodium dodecyl sulfate are weighed and added to 1000 to 2000 parts of deionized water, and after stirring evenly, 1 to 5 parts of molybdenum disulfide precursor, 1 to 3 parts of modified molybdenum disulfide and 1 to 2 parts of carbide are added, and stirred for 1 to 2 hours to obtain an electrolyte; Step S4: using a 10×10 mm nickel foam as a cathode, a 20×20 mm nickel plate as an anode, and the electrolyte described in step S3 to form an electrodeposition system, and performing an electrodeposition reaction for 1 to 5 minutes under a 0.1 to 0.5 A constant current DC power supply; Step S5: After the electrodeposition reaction in step S4 is completed, the cathode is recovered and washed with anhydrous ethanol and deionized water in sequence, and then the cathode is heat-treated to obtain a composite electrodeposition nanocatalyst; The modified molybdenum disulfide in step S3 is carbon-modified molybdenum disulfide and oxygen-modified molybdenum disulfide; the mass ratio of the carbon-modified molybdenum disulfide to the oxygen-modified molybdenum disulfide is (1-2):1; The preparation method of the carbon-modified molybdenum disulfide is as follows: by weight, 3 to 5 parts of sulfur powder are weighed and added to 12 to 15 parts of octylamine. After stirring for 5 to 10 minutes, 8 to 10 parts of molybdenum trioxide and 15 to 20 parts of anhydrous ethanol are added and stirred for 10 to 20 minutes to obtain a light yellow solution, which is kept at 150 to 160°C for 24 to 36 hours, cooled to room temperature, washed with deionized water, and then dried at 60 to 70°C under vacuum for 12 to 18 hours to obtain a primary product; 40 to 50 parts of the primary product and 60 to 80 parts of glucose are weighed and added to 100 to 120 parts of anhydrous ethanol, first ultrasonicated for 0.5 to 1 hour, then stirred for 1 to 2 hours, and the precipitate is collected by centrifugation; the precipitate is dried at 60 to 70°C under vacuum for 10 to 12 hours, and then heated to 700 to 800°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept for 2 to 3 hours, and cooled to room temperature to obtain carbon-modified molybdenum disulfide; The preparation method of the oxygen-modified molybdenum disulfide comprises the following steps: adding 10 to 30 parts of ethylene glycol to 40 to 60 parts of deionized water by weight, stirring evenly, adding 2 to 4 parts of ammonium molybdate and 6 to 7 parts of thiourea, stirring for 1 to 2 hours to obtain a mixed solution; reacting the mixed solution at 200 to 220° C. for 16 to 20 hours, washing the product with deionized water after the reaction is completed, and then vacuum drying at 60 to 80° C. for 6 to 8 hours to obtain oxygen-modified molybdenum disulfide; In step S3, the carbides are tungsten carbide and molybdenum carbide; the mass ratio of tungsten carbide to molybdenum carbide is (1-2):1; The nickel foam in step S4 is boron-modified nickel foam; the preparation method of the boron-modified nickel foam is as follows: by weight, 35-40 parts of ammonia water, 50-60 parts of ammonium chloride, 10-15 parts of cobalt chloride and 8-10 parts of nickel chloride are added to 150-200 parts of deionized water, and stirred to obtain a mixed solution A; 10-20 parts of sodium borohydride and 8-10 parts of sodium hydroxide are added to 150-200 parts of deionized water, and stirred to obtain a mixed solution B; 10-20 parts of nickel foam are soaked in 150-200 parts of mixed solution A for 5-10 minutes, and then 150-200 parts of mixed solution B are added, and the reaction is carried out for 10-20 minutes. After the reaction is completed, the product is washed with deionized water, and then dried at 30-35° C. under vacuum conditions for 24-30 hours to obtain the boron-modified nickel foam.
2. The method for preparing a composite electrodeposition nanocatalyst according to claim 1, characterized in that: The reaction temperature of the hydrothermal reaction in step S2 is 120-200° C., and the reaction time is 6-16 hours; the drying temperature is 60-90° C., and the time is 12-24 hours.
3. The method for preparing a composite electrodeposition nanocatalyst according to claim 1, characterized in that: The heat treatment temperature in step S5 is 60-90° C. and the time is 2-6 hours.
4. A composite electrodeposition nanocatalyst, characterized in that: Prepared according to the method according to any one of claims 1 to 3.
Citation Information
Patent Citations
Foamed nickel supported Ru-based catalyst, preparation method thereof and application of catalyst in hydrogen production by electrolysis of water
CN117966193A
Preparation method of molybdenum dioxide / carbon / foamed nickel composite hydrogen evolution catalyst
CN118028858A
Porous nickel-molybdenum-cobalt hydrogen evolution electrode, preparation method therefor and application thereof
WO2023143578A1